Respiratory-deficient mutants of Torulopsis glabrata, a yeast with circular mitochondrial deoxyribonucleic acid of 6 mu m. - O'Connor, R M (1976)
Purified mitochondria from the petite positive yeast Torulopsis glabrata contain a circular deoxyribonucleic acid (DNA) with a length of 6 mum and a buoyant density of 1.686 g/cm3. This DNA is absent from ethidium bromide induced respiratory-deficient mutants.